Cambodia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
This paper discusses major macroeconomic issues confronting Cambodia. The report also discusses recent growth performance of the economy and presents recently updated national accounts estimates. Revenue mobilization remains a key objective since, despite recent significant improvements, revenue performance is still low by international standards. The costs and benefits of a high degree of dollarization are briefly discussed. Export performance and trade policy are also reviewed. Maintaining export growth will depend on maintaining Cambodia's commitment to an open trade and exchange system.